The impact of elevated pulmonary artery pressure on exercise responses - Fowler, Robin (Curtin University, 2012)
Background and research questions. The four studies reported in this thesis investigated the implications of an elevated pulmonary artery pressure (PAP) on the response to an exertional challenge. The level of symptoms and exertion that healthcare professionals consider appropriate for patients with pulmonary arterial hypertension (PAH) was explored in the first study. In studies two, three, and four, exercise responses and exercise testing were evaluated in individuals with an elevated PAP on exercise, but a normal PAP at rest (exercise-induced pulmonary arterial hypertension, [EIPAH]).The following research questions were addressed: 1. Is there consistency in the advice given by healthcare professionals in Australia regarding physical exertion and symptoms, and in referral for exercise rehabilitation, for patients with PAH? 2. What are the clinical implications of an elevated PAP in symptomatic individuals with risk factors for PAH but who have a normal PAP at rest (EIPAH)? 3. Can the six-minute walk test (6MWT) identify reduced exercise capacity and accurately estimate aerobic capacity in individuals with EIPAH? 4. Are the haemodynamic and symptomatic responses to maximal and submaximal resistance exercise similar to the responses demonstrated during comparable intensities of aerobic exercise in individuals with EIPAH?Abstracts for the reported studies. This PhD program formed the basis for four publications in peer reviewed, international, scientific journals. These four publications are summarised, in abstract form, below. The full manuscripts of these publications constitute Chapters 4-7 of this thesis.